Exploring The Roots Of Justice : The Contribution Of Islamic Theology And Philosophy To Global Ethical Discourse - Ega Rismasita; Siska Septia Ulfa; Yulia Tri Samiha (Universitas Sains dan Teknologi Komputer, 2025)
Amidst global challenges such as economic disparity, intercultural conflicts, and environmental crises, the dominant narrative of justice is often confined to the secular Western framework. In the face of these global challenges, Islamic Theology and Philosophy offer a unique theocentric perspective that not only complements but also critiques the limitations of current global ethical frameworks. From a theological standpoint, key concepts such as Al-Adl (Divine Justice), particularly within the Mutazilah and Ash'ariyah schools, are analyzed to illustrate how divine justice serves as a moral imperative for human action, establishing principles of universality, equality, and accountability. In Islamic understanding, justice extends beyond the distribution of resources; it encompasses cosmic balance (Mizan) and the proper placement of all things in their rightful context. Meanwhile, Islamic Philosophy, especially through the thought of Al-Farabi and Ibn Sina on the concept of Al-Madinah Al-Fadilah (the Virtuous Society), provides an operational framework for implementing justice within social and political structures. The concept of Maqasid Al-Shariah, or the objectives of Islamic law, is elaborated as an ethical-legal methodology aimed at protecting five essential interests: religion, life, intellect, lineage, and property. This framework offers a basis for a global ethics centered on the protection of universal human dignity (Karamah Insaniyyah). This study employs textual and comparative analysis to synthesize these concepts and place them in dialogue with modern theories of global justice, such as those of Rawls and Sen. It concludes that Islamic contributions are vital in injecting spiritual, communal, and transcendent dimensions of accountability into global ethics, making it more holistic and inclusive. This encourages a re-reading of Islamic sources not merely as a heritage of the past, but as an active resource for shaping a more just future.